PENGEMBANGAN KREATIVITAS SISWA SEKOLAH DASAR MELALUI PEMBELAJARAN MATEMATIKA OPEN-ENDED - Rudyanto, Hendra Erik (Premiere Educandum, 2013)
Creativity of learners has become more and more important in the eraÂ of glabal competition, because the complexity of problems of all aspects Â in Â the Â modern Â era Â keeps Â on Â increasing all Â the Â time. Â The teaching and learning mathematics at the elementary school has to give Â the Â positive Â contribution Â so Â as Â to Â encourage Â the Â studentsâ creativity as optimally as possible. Open ended technique of teaching and learning mathematics can assumptively give alternatives of theÂ âtrueâ solutions to students by experiencing investigation against mathematic problems using their deep thnking skill, so that they can construct alternatives of solution creatively.Â Key words:Â Â Creativity, Â Open Â Ended Â Technique Â of Â Teaching Â andLearning Mathematics